Magnetostatic Interactions Between Wire-Tube Nanostructures - Escrig-Murua, J; Palma-Solorza, J; Salazar-Aravena, D (American Institute of Physics, 2015)
We have investigated the magnetostatic interactions between wire-tube nanostructures. We have observed that the coercivity of the array decreases when the distance between the nanostructures decreases. Besides, when the external magnetic field is applied along the axis of the nanostructures, the two Barkhausen jumps observed for an isolated wire-tube nanostructure give rise to several minor jumps for a weakly interacting array, which eventually become a single jump for the most interacting case. Additionally, the angle θ at which maximum coercivity is obtained varies as a function of the center-to-center distance between the nanostructures, while those remanences obtained for arrays with different distances between the nanostructures coincide. In this way, the study of magnetostatic interactions between wire-tube nanostructures is an interesting topic of research in connection with potential applications where it is usually desirable to avoid such interactions or at least control them. © 2015 AIP Publishing LLC.